Chronic cervicitis: role of adult autologus stem cells - Jain, Mayank; Jain, Sapna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Stem cells are biological cells found in all multi-cellular organisms and capable to differentiate into diverse specialized cell types and self-renew to produce more stem cells. Stem cells act as immuno-modulatory, angiogenetic, cell repairing and cell protecting agents. They also have strong anti-inflammatory effect due to paracrine action of trophic factors release. Chronic cervicitis is very common disease of adult women worldwide, chronic infection and inflammation of the cervix is hard to cure with high recurrence rate leading to long term consequences like pelvic inflammatory disease, infertility, ectopic pregnancy, chronic pelvic pain, increased predisposition to HPV and HIV infection and even can be a precursor of cervical cancer. Methods: To show the therapeutic and symptomatic benefits of these cells in chronic cervicitis we injected 10 patients with adult autologus stem cells (AASCs) locally in the cervix, and PRP, growth factors IV. All the cells were harvested from bone marrow after bone marrow aspiration. Results: Clinical benefits were evident on follow up visits in the entire treated patient. All the patient had shown improvement in symptoms like continuous malodourous discharge, dyspariunea, pelvic pain and pressure, backache, itching and burning, post coital bleeding. Conclusions: Present study have shown that AASCs and growth factors is a safe effective ethical and viable option not only to cure the disease but also in improving the quality of life of a woman and protecting her from its significant consequences.